Anatomy of the ventricular system: Historical and morphological aspects - Roberto Alexandre Dezena; Tareq A Juratli; Paulo Henrique Pires de Aguiar; Raphael Guerra David Reis; João Pedro de Oliveira Jr; Osei Yaw Nyarko; Leonardo Noronha Queiroz Santos; Pedro Henrique Simm de Pires de Aguiar (Brazilian Society for Pediatric Neurosurgery, 2020)
From the first description of the human ventricular system occurred in the 3rd century B.C. to modern neuronavegated endoscopy, neurosurgical knowledge evolved exponentially allowing safer approaches to the ventricular system. The present paper describes the historical aspects of ventricular system anatomy and its macroscopic and endoscopic anatomy from the Lateral ventricles to the third ventricle, describing in detail its structure and anatomical relationships.